Advances in computers. - Memon, Atif M. (Academic Press is an imprint of Elsevier, 2019)
Advances in Computers, Volume 112, the latest volume in a series published since 1960, presents detailed coverage of innovations in computer hardware, software, theory, design and applications. Chapters in this updated volume include Mobile Application Quality Assurance, Advances in Combinatorial Testing, Advances in Applications of Object Constraint Language for Software Engineering, Advances in Techniques for Test Prioritization, Data Warehouse Testing, Mutation Testing Advances: An Analysis and Survey, Event-Based Concurrency: Applications, Abstractions, and Analyses, and A Taxonomy of Software Integrity Protection Techniques. Provides in-depth surveys and tutorials on new computer technology Covers well-known authors and researchers in the field Presents extensive bibliographies with most chapters Includes volumes that are devoted to single themes or subfields of computer science.